ONLINE LEARNING EVALUATION OF PAI CLASS 5 STUDENTS MIN 1 LANGSA - rahma siti (lppm Universitas Negeri Jakarta, 2021)
ABSTRACT Education is the process of changing the attitude and behavior of a person or group for the better through teaching / guidance and training. In the process, the teacher plays an important role in the delivery of material so that it has an influence on the success of their students. The subject learning of PAI (Islamic education) at MIN 1 Langsa is currently less effective and efficient due to the Covid-19 pandemic (corona virus disease) which makes teachers and students unable to meet face to face directly. Students asked to learn from home using online media.Online learning is undirect face-to-face learning between teachers and students by accessing internet networks and using social media to interact or exchange information. This study aims to describe the online learning of Islamic Education lessons at MIN 1 Langsa. The research approach is descriptive qualitative using primary and secondary data sources. The data collection uses the method of observation, documentation and interviews. The analysis of data using reduction, display data and conclusion.The result of the research showed that online learning PAI lessons carried out at MIN 1 Langsa used the Whatsapp application. Students at home are accompanied by their parents in studying the material and exercises provided by their teachers through the Whatsapp application. Because learning is done online, teachers must be more thorough and focused in evaluating learning activities. Students also complained that they had difficulties with poor internet networks. Some of them also do not have cell phones based on Android and some are not proficient in using them, it is making the learning process ineffective.Keywords:            learning, online, students